Using Shainin DOE for Six Sigma: an Indian case study. Issue 2 (25th January 2016) - Prashar, Anupama
Abstract : Shainin design of experiments (DOE) offers a powerful and effective experimental design approach for solving the chronic quality problems that plague manufacturers worldwide. However, the academic literature still contains a few empirical studies on the use of non-statistical Shainin DOE tools to simplify the quality improvement initiatives. In order to overcome this deficiency, this case describes framework for incorporating Shainin experimental design within Six Sigma define–measure–analyse–improve–control and tests its effectiveness in an Indian automotive gear manufacturing unit. Shainin tools such as Paired Comparison, Product/Process search, Concentration chart, B vs. C analysis, Pre-control chart were employed to analyse, improve and control the gear manufacturing process. The study provides stimulus for the wider application of Shainin experimental design approach for industrial experimentation.